The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1590/1414-462x202199010420
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with use of assistive walking devices among older adults in Brazil

Abstract: Background Walking devices and other forms of assistive technology (AT) can benefit older adults by supporting mobility and social interactions, but usage outside of high-income countries is generally low. Objective To examine the factors associated with AT use and whether AT use is associated with higher levels of social participation among older adults in Brazil. Method The 2013 Brazilian National Health Survey interviewed 23,815 individuals 60 years or older. Descriptive and logistic regression analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
3
2
Order By: Relevance
“…One possible explanation for this discrepancy could be that they included all elderly people in their study while all the participants in our study had a disability and therefore were more likely to expect to possess and use a greater number of assistive devices. Similarly, the use rate of assistive devices among elderly people with mobility difficulties in Brazil was 34% (Andrade et al, 2021), which was lower than our research data.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…One possible explanation for this discrepancy could be that they included all elderly people in their study while all the participants in our study had a disability and therefore were more likely to expect to possess and use a greater number of assistive devices. Similarly, the use rate of assistive devices among elderly people with mobility difficulties in Brazil was 34% (Andrade et al, 2021), which was lower than our research data.…”
Section: Discussioncontrasting
confidence: 87%
“…One possible explanation for this discrepancy could be that they included all elderly people in their study while all the participants in our study had a disability and therefore were more likely to expect to possess and use a greater number of assistive devices. Similarly, the use rate of assistive devices among elderly people with mobility difficulties in Brazil was 34% (Andrade et al., 2021), which was lower than our research data. This difference might be attributed to variations in the types of assistive devices used, differences among patient populations (such as age, disease type, and severity), and even variations in healthcare systems across different countries (Andrade et al., 2021; De Boer et al., 2009; Dupraz et al., 2020; Löfqvist et al., 2005; Pilegaard et al., 2022; Pryor et al., 2018; Yu et al., 2022).…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…On the health aspect, the majority of them have hypertension and BMI preobese (25.0 -29.9 kg/m 2 ). Previous research has revealed that most people who use walking aids are elderly people aged 60 and above (Andrade et al, 2022;Charette et al, 2018). Decisions to use walking aids are also based on beliefs about ageing as well as physical needs (Gooberman-Hill & Ebrahim, 2007).…”
Section: 1mentioning
confidence: 99%